A chromosome-level reference genome of non-heading Chinese cabbage [Brassica campestris (syn. Brassica rapa) ssp. chinensis]. (28th December 2020) - Li, Ying; Liu, Gao-Feng; Ma, Li-Ming; Liu, Tong-Kun; Zhang, Chang-Wei; Xiao, Dong; Zheng, Hong-Kun; Chen, Fei; Hou, Xi-Lin
Abstract: Non-heading Chinese cabbage (NHCC) is an important leafy vegetable cultivated worldwide. Here, we report the first high-quality, chromosome-level genome of NHCC001 based on PacBio, Hi-C, and Illumina sequencing data. The assembled NHCC001 genome is 405.33 Mb in size with a contig N50 of 2.83 Mb and a scaffold N50 of 38.13 Mb. Approximately 53% of the assembled genome is composed of repetitive sequences, among which long terminal repeats (LTRs, 20.42% of the genome) are the most abundant. Using Hi-C data, 97.9% (396.83 Mb) of the sequences were assigned to 10 pseudochromosomes. Genome assessment showed that this B. rapa NHCC001 genome assembly is of better quality than other currently available B. rapa assemblies and that it contains 48, 158 protein-coding genes, 99.56% of which are annotated in at least one functional database. Comparative genomic analysis confirmed that B. rapa NHCC001 underwent a whole-genome triplication (WGT) event shared with other Brassica species that occurred after the WGD events shared with Arabidopsis . Genes related to ascorbic acid metabolism showed little variation among the three B. rapa subspecies. The numbers of genes involved in glucosinolate biosynthesis and catabolism were higher in NHCC001 than in Chiifu and Z1, due primarily to tandem duplication. The newly assembled genome will provide an important resource for research on B. rapa, especially B. rapa ssp. chinensis .